Peran Pembiasaan Membaca Asmaul Husna dan Bacaan Shalat Pra Kegiatan Belajar Mengajar dalam Pembentukan Karakter Islami Siswa di SDN Purwoyoso 03 - Handrini, Lilis; A, Arsanshanie; Khasanah, Ibadul; Nasikhah, Fithrotun; Syah, Mohchammad Kurniawan; Rahmani, Sabila (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to describe the implementation and impact of the habituation of reciting Asmaul Husna and prayer readings before learning activities in shaping students’ Islamic character at SDN Purwoyoso 03 Semarang. The background of this study is the importance of character education that integrates spiritual and psychological values from an early age, especially in public elementary schools. Using a qualitative descriptive approach with a case study design, data were collected through observation, interviews, and documentation. The results show that the habituation activities were carried out regularly every Tuesday and Wednesday morning and involved students from grades 3 to 6 as rotating leaders. These routines instilled values such as discipline, responsibility, confidence, and religiosity. The role of teachers was central in mentoring, while school leadership provided full support for the program’s sustainability. Furthermore, parents expressed positive responses and felt that the spiritual training at school complemented religious education at home. This study confirms that consistent spiritual habituation contributes positively to students’ cognitive, affective, and psychomotor development. It also highlights the importance of synergy between school and family in character building. The findings of this research offer valuable insights into the practical integration of Islamic values into school culture and demonstrate the effectiveness of religious routines as a strategy for character formation in elementary education.